Odpowiedzi

2010-02-03T16:38:40+01:00
A)2x-(x+1)=2x-x-1=x-1
b)(8x-1)-(5x-4)=8x-1-5x+4=3x+3
c)-(2x-2y+2xy)-(4x-2y)=-2x+2y-2xy-4x+2y=-6x+4y-2xy
d)3x-(4x-(2x+1)-3) =3x-(4x-2x-1-3)=3x-2x+4=x+4
Najlepsza Odpowiedź!
2010-02-03T16:42:22+01:00
A)2x-(x+1)= 2x-x-1=1x-1
b)(8x-1)-(5x-4)=8x-1-5x+4=3+3x
c)-(2x-2y+2xy)-(4x-2y)=-2x+2y-2xy-4x+2y= -6x+4y-2xy
d)3x-(4x-(2x+1)-3)=3x-4x+6x+3=7x+3
;)
2010-02-03T16:47:48+01:00
A)2x-(x+1)=2x-x-1=x-1
b)(8x-1)-(5x-4)=8x-1-5x+4=3x+3
c)-(2x-2y+2xy)-(4x-2y)=-2x+2y-2xy-4x+2y=-6x+4y-2xy
d) 3x-(4x-(2x+1)-3)=3x-(4x-2x-1-3)=3x-4x+2x+1+3=x=4